HIGHER EDUCATION AND LABOUR MARKET IN UKRAINE: A DECADE OF INTERACTION - Mospan, Natalia (Educological discourse, 2021)
The national model of interaction between higher education and the labour market was formed under the influence of world processes (globalization, marketization, internationalization, Europeanization). In 2020, the national economy, having reached the frontier of its development, was struck by the COVID-19 pandemic, whose negative consequences require rigorous analysis and careful study. Since 2014, the negative trends in the interaction of higher education with the labour market have begun to grow. They manifested in a shortage of highly qualified workers, or inconsistency of qualifications with the requirements of the national labour market. These trends continue to escalate in recent years. At the legislative level, there was an attempt from the government to outline steps towards the interaction of higher education with the labour market but without defining specific mechanisms. The economic and financial crisis has required the government to transit to another form of financing higher education institutions and to restructure and even reduce their number. The current state of interaction between higher education and the labour market is defined as unbalanced. That has led to a mismatch between supply and demand in the national labour market; the high level of unemployment among graduates of higher educational institutions and professionals with higher education; increasing student and labour migration; distance learning and work remotely. Ukraine is gradually losing modern factors of economic growth – human capital. Prospective trends are considered in the transition to a circular economy; the inclusion of the “environmental” dimension of the circular economy in professionals training and education. The article analyses the interaction of higher education with the labour market in Ukraine over the past decade (2010-2020). The study focuses on an analysis of past, current and future trends in higher education, the labour market and national legislation from the perspective of sustainable economic development. The research is interdisciplinary and mixed (theoretical and empirical). For visualization of the analysed phenomena and conclusions, the surveys data conducted in 2015, 2017 and 2020 are presented.